2013
DOI: 10.1590/s1413-81232013000600034
|View full text |Cite
|
Sign up to set email alerts
|

Apoio social e síndrome da fragilidade em idosos residentes na comunidade

Abstract: Frailty among the elderly is a result of the complex interplay between social and clinical factors involved in its genesis. However, it is still unclear whether the fraailty syndrome can be aggravated due to lack of social support. The scope of this study was to analyze the association between social support and the frailty syndrome among elderly residents in the community. It is an analytical observational cross-sectional study, with a sample of 300 elderly people. Socio-demographic, economic and physical hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
3
7
1
6
Order By: Relevance
“…Evaluating the characteristics of care, caregivers living in areas of high social vulnerability received less material and emotional help, which corroborates findings in a study carried out in the Municipality of Natal (Rio Grande do Norte state) with 300 elderly people, where the elderly presented a weak support network, often only offered by some neighbors (20) . Another study identified that elderly people living in regions of high vulnerability have a large social network; however, only a few members play a functional role, that is, providing or receiving support (21) .…”
Section: Discussionsupporting
confidence: 83%
“…Evaluating the characteristics of care, caregivers living in areas of high social vulnerability received less material and emotional help, which corroborates findings in a study carried out in the Municipality of Natal (Rio Grande do Norte state) with 300 elderly people, where the elderly presented a weak support network, often only offered by some neighbors (20) . Another study identified that elderly people living in regions of high vulnerability have a large social network; however, only a few members play a functional role, that is, providing or receiving support (21) .…”
Section: Discussionsupporting
confidence: 83%
“…(11) In addition, the elderly with low educational level may present mental health problems, chronic conditions, in addition to social exclusion, less access to information, and unfavorable socioeconomic conditions. (21) Regarding the current occupation, there was a predominance of retired elderly, of which 137 (55.4%) were found in this study. Retirement, pensions, and government benefits are the main sources of income and support for the elderly in the Brazilian population.…”
Section: Discussionmentioning
confidence: 47%
“…A classificação da fragilidade encontrada no presente estudo apresentou-se próxima das demais pesquisas relacionadas (Amaral et al, 2013;Espinoza et al, 2010;Freiheit et al, 2011). Vieira e colaboradores (2013) identificaram que os idosos pré-frágeis e frágeis apresentaram, respectivamente, maiores e crescentes razões de chances para dependência em atividades instrumentais de vida diária; restrição em atividades avançadas de vida diária; utilização de dispositivos auxiliares da marcha; comorbidades; quedas; sintomas depressivos; menor autoeficácia para prevenir quedas; hospitalização e idade avançada.…”
Section: Discussionunclassified